The Psychoactive Agent Crocin Can Regulate Hypothalamic-Pituitary-Adrenal Axis Activity - Asalgoo, Sara; Tat, Mahdi; Sahraei, Hedayat; Pirzad Jahromi, Gila (Frontiers in Neuroscience, 2017)
Posttraumatic stress disorder (PTSD) occurs following life threatening events. The activity of hypothalamic-pituitary-adrenal (HPA) axis, which serves as the first line of defense against stress, is damaged in disorder. The current study aimed to investigate the role of crocin in the improvement of HPA function in the animal model of PTSD induced by electric foot shock. Rats treated with crocin 5 minutes prior to the induction of stress. Samples were placed again in the communication box after 21 days, as re-experience and we followed individual behaviors such as sniffing, rearing, grooming, and freezing. Also, plasma levels of corticosterone were assessed in the cases using ELISA. On day 28, after rats were weighed and sacrificed, adrenal and thymus glands were removed and were weighed to evaluate the quantitative expression of Corticotrophin release hormone (CRH), Glucocorticoid Receptor (GluR), and Arginine Vasopressin (AVP) genes by Real time RT-PCR. Our data demonstrated that rats exposed to a reminder of the stressor developed characteristic symptoms of PTSD and predictive (response to crocin) validities. Based on these validities we identified significant changes in the CRH gene in the hypothalamus, GluR in the pituitary regions, the level of plasma corticosterone and behavior freezing in PTSD-model rats, which were treated with crocin. Together, these findings point to an interactive relationship of treatment of crocin with changes of HPA axis in PTSD. It may serve an appropriate preventive treatment for population exposed to a traumatic event.